Destabilisation of bank deposits across destinations: Assessment and policy implications - Ulrich Bindseil; Richard Senner (European Central Bank (ECB), 2024)
Rapid and large deposit outflows from banks have regained attention in the context of the March 2023 demises of Credit Suisse, SVB and other regional US banks. Moreover, the possible introduction of CBDC or a marked success of stablecoins are perceived as additional clouds over the future of deposit funding. While the bank run literature rarely pays attention to where bank deposits can flow to, this paper distinguishes the different flow of funds mechanics across all possible destinations and reviews for each the current and prospective future factors that may contribute to the observed increase of the speed and size of bank runs. While some of these factors can be contained through policy measures, others, like the intensified competition between banks will inevitably stay, and bank balance sheet management and liquidity regulation need to accept the new normal of somewhat less stable and more expensive sight deposits.
Keywords: E42; E51; G21; G23; 330; bank funding; bank runs; flows of funds; financial stability; liquidity crisis